Georgia and New Hampshire (Document (Virginia. General Assembly) ;, 1843)
1843 state resolutions transmitted to the Virginia General Assembly by Virginia Governor Ja. M'Dowell. The Georgia resolutions were against the repudiation of state debts and Massachusetts' assertion that free blacks are citizens; the New Hampshire resolution was against the established franking system and for a reduction of letter postage.